2010
DOI: 10.1007/s00399-010-0088-8
|View full text |Cite
|
Sign up to set email alerts
|

Atrial-selective drugs for treatment of atrial fibrillation

Abstract: Atrial fibrillation (AF) is accompanied by a high risk of thromboembolic complications necessitating anticoagulation therapy. Arrhythmias have a high tendency to become persistent. Catheter ablation techniques are highly effective in the treatment of AF; however, these procedures are far too costly and time-consuming for the routine treatment of large numbers of AF patients. Moreover, many patients prefer drug treatment although conventional antiarrhythmic drugs are moderately effective and are burdened with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Constitutively active I K,ACh has been demonstrated in patients with persistent AF, where it may contribute to sustaining the arrhythmia (8). An increase in constitutively active I K,ACh has also been demonstrated in the canine atrial tachycardia-remodeled left atrium, and recent studies (16,24,27) have suggested that inhibition of I K,ACh may offer an atrium-specific target for the treatment of AF.…”
mentioning
confidence: 99%
“…Constitutively active I K,ACh has been demonstrated in patients with persistent AF, where it may contribute to sustaining the arrhythmia (8). An increase in constitutively active I K,ACh has also been demonstrated in the canine atrial tachycardia-remodeled left atrium, and recent studies (16,24,27) have suggested that inhibition of I K,ACh may offer an atrium-specific target for the treatment of AF.…”
mentioning
confidence: 99%
“…Taking these factors into consideration, we may say that atrial tissue will recover faster from inactivation (due to its less negative membrane potential), therefore I Na blockers—which binds preferably to inactivated channel state—will exhibit a larger blocking effect in atria than in ventricles [ 104 ]. For additional discussion, also compare Ravens and Christ [ 106 ].…”
Section: Therapeutic Options To Prevent and Stop Atrial Remodellingmentioning
confidence: 99%
“…As mentioned above, various potassium channels are remodeled during AF and several of them are almost only expressed in the atria (I Kur , I K,ACh , I K,2P , and I K,Ca ) ( Ravens and Christ, 2010 ; Hancox et al, 2016 ). Pharmacological inhibition of these channels prolongs the AP and therefore extends the atrial ERP.…”
Section: Computational Pharmacology In Afmentioning
confidence: 99%